Bentuk Musik Saluang Sirompak Versi Abah Emi Pada Acara Alek Pemuda Di Parik Dalam Nagari Taeh Baruah Kabupaten 50 Kota Payakumbuh - Rama Kurniawan; Syeilendra Syeilendra (SENDRATASIK UNP, 2021)
This study aims to describe Saluang Sirompak music of Abah Helmi version at Alek Pemuda event in Parik Dalam, Taeh Baruah village, Lima Puluh Kota regency, Payakumbuh City. This research belongs to a qualitative research using a descriptive approach. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing tools and cameras. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted by collecting the data, clarifying the data, and summarizing the data. The results show that Saluang Sirompak of Abah Emi version is a folk performance art which is previously used as a ritual mean. Its song is in the form of a rhyme accompanied by Saluang and Gasiang Tangkurak musical instruments. There is no difference between the previous and current Saluang Sirompak song text anad between the old and present Saluang melodies. The use of the term Saluang Sirompak comes from the word Rompak /Rampok, so the lyrics are related to someone's desire to own someone by force. The musical form of Saluang Sirompak is a combination of Dendang accompanied by two musical instruments: Saluang Sirompak and Gasiang Tangkurak which form a complete unit. The music consists of three parts: part one (opening) of Saluang Sirompak and Gasiang Tangkurak instruments, part two (content) of Dendang accompanied by Saluang and Gasiang Tangkurak instruments, part three (closing) of saluang sirompak and gasiang tangkurak instruments. The music in Saluang Sirompak show has a minimum duration of 20 minutes. It starts with the Gasiang player who screams as a symbol of the beginning of part one. Dendang on Saluang Sirompak music is in the form of rhyme repeated alternately between one singer and another by singing one song, and this is the part two (content) of Saluang Sirompak music.